Performance of traditional risk factors in identifying a higher than expected coronary atherosclerotic burden - Dores, Hélder (2015)
Abstract Objective To evaluate the performance of traditional cardiovascular (CV) risk factors in identifying a higher than expected coronary atherosclerotic burden. Methods We assessed 2069 patients undergoing coronary CT angiography, with assessment of calcium score (CS), for suspected coronary artery disease. A higher than expected atherosclerotic burden was defined as CS >75th percentile (CS >P75) according to age and gender-adjusted monograms. The ability of traditional CV risk factors to predict a CS >P75 was assessed in a customized logistic regression model ("Clinical Score") and by the calculation of SCORE (Systemic Coronary Risk Evaluation). The population attributable risk (PAR) of risk factors for CS >P75 was calculated. Results The median CS was 3.0 (IQR 0.0-98.0); 362 patients had CS >P75. The median SCORE was 3.0 (IQR 1.0-4.0). With the exception of hypertension, all traditional CV risk factors were independent predictors of CS >P75: diabetes, dyslipidemia, smoking and family history (OR 1.3-2.2, p≤0.026). The areas under the ROC curves for CS >P75 were 0.64 for the Clinical Score (95% CI 0.61-0.67, p<0.001) and 0.53 for SCORE (95% CI 0.50-0.56, p=0.088). About a quarter of patients with CS >P75 were in the two lower quartiles of the Clinical Score. Altogether, the traditional risk factors explain 56% of the prevalence of CS >P75 (adjusted PAR 0.56). Conclusion Despite the association of CV risk factors with a higher than expected atherosclerotic burden, they appear to explain only half of its prevalence. Even when integrated in scores, the predictive power of these risk factors was modest, exposing the limitations of risk stratification based solely on demographic and clinical risk factors.